The Influence of Profitability, Solvency, Liquidity Ratios on Company Value: Study on Manufacturing Companies in The Food and Beverage Sub-Sector Listed on The IDX for The 2019-2023 Period - Khumairo Annisa Annisa; Pristin Prima Sari; Johannes Maysan Damanik (PT SOLUSI EDUKASI BERDIKARI, 2024)
This study aims to determine the effect of profitability, solvency, liquidity on company value in food and beverage sub-sector manufacturing companies listed on the IDX for the 2019-2023 period. This study is a quantitative study using secondary data obtained from the financial statements of food and beverage sub-sector manufacturing companies listed on the IDX for a period of 5 years. The data in this study were processed using IBM SPSS 27.0 Statistics. The results of this study indicate that profitability has a positive effect on company value, solvency does not affect company value, liquidity has a positive effect on company value.